The Lakescape in the Eyes of a Tourist - Potocka, Ilona (Quaestiones Geographicae, 2013)
Visual-esthetic landscapes values are determining a comfort of leisure in the environment, forms of tourist activities and constitute value as such. The aim of the research is to define how, and which components of lakescape are perceived by tourists, and how it influences on lake tourist activity. Presented paper describes also the role of water itself and the importance of the aesthetics of lakescape in tourist experience. The research of visual landscape values has been conducted for a long time, using different methods. The paper describes, apart from traditional method of inquires, use of eye-tracking to define elements of lakescape perceived by tourists.